The Implementation of TPACK Learning in Human Movement Systems Materials to Improve Students’ Critical Thinking - Supiana Dian Nurtjahyani; Anik Winarni; Indra Sugiarsi; Restiani Agusvita; Ali Mustafa; Sukisno Sukisno (AL-ISHLAH: Jurnal Pendidikan, 2022)
Natural Sciences is the study of natural phenomena. In science learning, students are expected to have scientific knowledge, high-level thinking, critical and creative thinking, so that they become independent learners. The purpose of this study was to describe students' critical thinking skills through environmental-based TPACK learning on the human motion system material. This research method is done by lesson study with 3 learning cycles. The results showed that TPACK learning can improve students' critical thinking, especially in identifying, linking, analyzing and concluding in this study the application of TPACK learning to improve thinking skills in categories can be very good.